Chalazal seed coat development in Brassica napus. (December 2015) - Millar, Jenna L.; Khan, Deirdre; Becker, Michael G.; Chan, Ainsley; Dufresne, André; Sumner, Michael; Belmonte, Mark F.
Highlights: We provide the first anatomical characterization of the chalazal seed coat in Brassica napus. Xylem and phloem of the parental plant terminate in the CZSC of Brassica napus. Transcripts encoding genes involved in the transport of sugar, amino acids, and water are present within the CZSC of Brassica napus. Transcription factors LRL1, FUS3, and BZIP25 are co-expressed with genes involved in essential transport processes in the chalazal seed coat. Abstract: The chalazal seed coat (CZSC) is a maternal subregion adjacent to the funiculus which serves as the first point of entry into the developing seed. This subregion is of particular interest in Brassica napus (canola) because of its location within the seed and its putative contribution to seed filling processes. In this study, the CZSC of canola was characterized at an anatomical and molecular level to (i) describe the cellular and subcellular features of the CZSC throughout seed development, (ii) reveal cellular features of the CZSC that relate to transport processes, (iii) study gene activity of transporters and transcriptional regulators in the CZSC subregion over developmental time, and (iv) briefly investigate the contribution of the A and C constituent genomes to B. napus CZSC gene activity. We found that the CZSC contains terminating ends of xylem and phloem as well as a mosaic of endomembrane and plasmodesmatal connections, suggesting that this subregion is likely involved in the transport of material and information from the maternal tissues of the plant to other regions of the seed. Laser microdissection coupled with quantitative RT-PCR identified the relative abundance of sugar, water, auxin and amino acid transporter homologs inherited from the constituent genomes of this complex polyploid. We also studied the expression of three transcription factors that were shown to co-express with these biological processes providing a preliminary framework for the regulatory networks responsible for seed filling in canola and discuss the relationship of the CZSC to other regions and subregions of the seed and its role in seed development.